Suicide in young people aged 15-24: a psychological autopsy study. - Houston, K; Hawton, K; Shepperd, R (2001)
BACKGROUND: The suicide rate in young people in the United Kingdom has increased over the last decade. As there is a paucity of information about the characteristics of young suicides we have undertaken a detailed investigation of suicides in people aged 15-24 years by means of the psychological autopsy approach. METHODS: The sample consisted of 27 subjects (25 males, two females) whose deaths received a verdict of suicide (N=24) or undetermined cause (N=3). Information was collected from informant interviews, coroners' inquest notes, medical records and psychiatric case notes. A sub-sample of 22 male subjects was compared with an age-matched sample of male deliberate self-harm (DSH) patients. RESULTS: Psychiatric disorders were diagnosed in 19 (70.4%) subjects. These were most commonly depressive disorders (55.5%). Very few individuals were receiving treatment for their disorders. Substance abuse disorders were uncommon but a substantial proportion of individuals had problems with alcohol or drug misuse. Personality disorders were present in 29.6% of subjects and disorders or personality trait accentuation in 55.6%. Comorbidity of psychiatric disorders was found in a third of subjects. The suicides were often the end-point of long-term difficulties extending back to childhood or early adolescence. In addition to mental disorders, relationship and legal difficulties were identified as relatively common contributory factors to the suicides. In comparison to deliberate self-harm patients, male suicides were more likely to use dangerous methods and live alone. LIMITATIONS: Several potential informants could not be interviewed and there was no general population control sample. CONCLUSIONS: The process leading to suicide in young people is often long term, with untreated depression in the context of personality and/or relationship difficulties being a common picture at the time of death. The prevention of suicide in the young clearly requires multiple strategies.